How Local Art Made Australia's National Capital - Doyle Wawrzyńczak, Anni (ANU Press, 2020)
Canberra's dual status as national capital and local city dramatically affected the rise of a unique contemporary arts scene. This complex story, informed by rich archival material and interviews, details the triumph of local arts practice and community over the insistent cultural nation-building of Australia's capital. It exposes local arts as a vital force in Canberra's development and uncovers the influence of women in the growth of its visual arts culture. A broad illumination of the city-wide development of arts and culture from the 1920s to 2001 is combined with the story of Bitumen River Gallery and its successor Canberra Contemporary Art Space from 1978 to 2001. This history traces the growth of the arts from a community-led endeavour, through a period of responses to social and cultural needs, and ultimately to a humanising local practice that transcended national and international boundaries.